Ensuring excellence in patient care, research, and education: thoughts on leadership and teamwork - David A Spain (Trauma Surgery & Acute Care Open)
There are many ways to develop your leadership skills and many ways to be an effective leader. This is one perspective. The best style is the one that works for you and your environment. I would encourage you to spend some time and effort exploring your leadership style, develop new leadership skills, and look for opportunities to serve others.